High-Protein Dietary Supplementation and Nutritional Status Improvement of Malnourished Patients in Hospital Care - Marcellus Simadibrata; Fiastuti Witjaksono; Yohannessa Wulandari; Raja Mangatur Haloho; Rabbinu Rangga Pribadi; Murdani Abdullah; Aditya Rachman; Anthony Eka Wijaya; Batara Bisuk; Daniel Martin Simadibrata; Rizka Mutiara; Kaka Renaldi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Hospital malnutrition is common in Indonesia and other developing countries. In Asia, the prevalence of hospital malnutrition ranges between 27-39%. The causes of malnutrition in hospital care include insufficient food intake and increased catabolic processes due to underlying causes such as metabolic disease, infection, and malignancy. Several studies have demonstrated that malnutrition increases the morbidity and mortality of hospitalized patients, prolongs hospital stay, and delays recovery. Therefore, healthcare providers must recognize malnutrition early by conducting nutritional screening and assessment to prevent worsening of malnutrition and administer the optimal nutritional therapy to patients. Apart from giving a standard diet, high-protein food supplementation in liquid form remains a suitable alternative for patients, especially since it is easily digestible. A high protein diet is associated with a better mortality rate, better weight gain, and improved SGA score in patients.